CHARACTERISTICS OF THE DECISION-MAKING PROCESS IN THE PUBLIC VERSUS THE PRIVATE ENVIRONMENT - ANCA JARMILA GUŢĂ (Annals of the University of Petrosani: Economics)
Starting from the premise that any human activity practiced daily involves a continuous decision-making process because whatever we choose to do involves the adoption of a decision after evaluating several decision-making options that we often have at hand, the paper presents the peculiarities of the decision-making process in the public environment compared to the private one in our country. Whether the decision is taken in the public or private environment, this is the most essential element in the management activity of an organization without which managers could not exercise the management activity because the decision is directly related to all other elements related to the functioning and development of an organization/institution. The decision-making process is a complex process that takes place both in the public environment and in the public sector. in the same way, it is important to note that the following conditions are met this process, because their level of training accompanied by a vast amount of information is the most important elements needed for the decision to be taken in the best way and to achieve the objectives for which it was formulated.